The Effect of Dividend Policy, Capital Structure, Profitability, and Growth on Firm Value - Alfianita Alfianita; Perdana Wahyu Santosa (Journal of Accounting, Management, and Economics Research (JAMER), 2022)
This study aims to determine the effect of dividend policy, capital structure, profitability, and growth on firm value and its review from an Islamic point of view. The population in this study are all companies members of the LQ45 index on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique used is a purposive sample. The number of samples in this study was 16 companies. Data was collected using secondary data obtained from external data, namely the financial statements of LQ45 index companies listed on the Indonesia Stock Exchange in the 2015–2019 period. The data analysis method used is panel data regression analysis. The study results show that: (1) dividend policy does not affect firm value. (2) capital structure has a positive effect on firm value. (3) profitability has a positive effect on firm value. (4) growth partially does not affect firm value. Management should control a proportional debt policy to grow the firm's value on an ongoing basis and focus on increasing profitability through sales growth and cost-efficiency by increasing asset turnover and cost of debt efficiency. It is expected that firm value increase sustainability.